Macropelopia (Macropelopia) patagonica, a new Tanypodinae (Diptera: Chironomidae) from the Patagonian Andes - Da Silva, Fabio Laurindo; Pinho, Luiz Carlos (Zootaxa, 2020)
One new species of Macropelopia Thienemann (Diptera: Chironomidae: Tanypodinae), M. (Macropelopia) patagonica sp. n. is described and figured as adult male. The specimens were collected from the Patagonian Andes, at San Carlos de Bariloche, Argentina. In addition, the generic diagnosis of Macropelopia is emended for the adult male.